THE IMPORTANCE OF MERGING TRADITIONAL AND INNOVATIVE PEDAGOGY DURING A PANDEMIC (Education in the 21st Century, 2023)
The article provides the results of research in the field of the educational system, which is transforming in the context of a pandemic and is dynamically moving from traditional education to innovative. Innovative learning is presented in the context of adapting all aspects of the educational process to it: teachers, students and parents. Further, a rather good level of teachers' readiness for distance learning was indicated; it should be noted that problems did arise when switching to distance learning, to a greater extent, among teachers of the older age group. In the context of distance learning, parents play an important role in supporting their children, but even under the most favorable conditions, the overwhelming majority of parents are not sufficiently prepared to provide quality support. This picture shows that parents are not psychologically inclined to share responsibility for the moral state of their children together with the school, they are not capable of pedagogical interaction and support. The results obtained allow us to come to certain conclusions. Schools should take advantage of this situation to increase the effectiveness of development programs, the competence of the teaching staff, including the willingness of teaching teams to discuss (reflect, analyze) the results of their activities during this period. The experience gained requires a more thorough study, but one thing is clear: already at the present time it is necessary to change the content of the training of pedagogical personnel. Young specialists should not only know digital educational competencies, but also have a good command of them, be ready to work in conditions of “indirect” communication with children to provide them with help and support.
Keywords: Keywords: innovative pedagogy, traditional pedagogy, education in a pandemic, the introduction of innovative methods into the educational process, distance education, traditional education.